2021
DOI: 10.1186/s12873-021-00484-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the novel VieScope with conventional and video laryngoscope in a difficult airway scenario – a randomized, controlled simulation trial

Abstract: Background Endotracheal intubation continues to be the gold standard for securing the airway in emergency situations. Difficult intubation is still a dreadful situation when securing the airway. Objective To compare VieScope with Glidescope and conventional Macintosh laryngoscopy (MAC) in a simulated difficult airway situation. Methods In this randomized controlled simulation trial, 35 anesthesiologist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…On the other hand, intubation with the VSC required significantly more time than the conventional approach. So far, the VSC has only been studied in simulated airway scenarios (6)(7)(8). Although helpful in the initial assessment of new devices, manikin studies have limitations as, e.g., secretions obscuring the view on the larynx are often not adequately modeled (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, intubation with the VSC required significantly more time than the conventional approach. So far, the VSC has only been studied in simulated airway scenarios (6)(7)(8). Although helpful in the initial assessment of new devices, manikin studies have limitations as, e.g., secretions obscuring the view on the larynx are often not adequately modeled (15).…”
Section: Discussionmentioning
confidence: 99%
“…Feasibility of the VSC in normal and difficult airways has been evaluated in manikin studies with promising results ( 6 , 7 ) and the VSC has been shown to be superior to conventional DL during simulated cardiopulmonary resuscitation with providers wearing personal protective equipment ( 8 ). However, clinical studies comparing the VSC with DL as the current clinical standard technique are missing, so far.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, while certain interventions may be sound in the laboratory setting, real-life clinical settings may be complex to prove them in the field. There are multiple methods for oxygenation and ventilation 19 20 21 22 23 24 25 26 27 and multiple reasons to apply (moderate) PEEP levels in multiple trauma patients: one of the most important is the prevention of atelectasis resulting in less shunting volume and finally better oxygenation. Further, many multiple trauma patients suffer from severe thoracical trauma where PEEP may be lifesaving by alveolar stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…It allows direct visualisation of the glottis and aids endotracheal intubation using a bougie. [ 32 ] The infrared red intubation system (IRRIS) consists of a small infrared light source placed on the anterior cervical surface and over the cricothyroid membrane. The device emits infrared red light through the skin of the patient to the subglottic space.…”
Section: Newer Tools and Techniques For Airway Managementmentioning
confidence: 99%